Birdie Danse Macabre - Kargotis, Demetrios; Mortimer, Nicholas; Macdonald, Dash (My University, 2024)
This practice-based research presentation, delivered as a three-act performative lecture, explored contemporary adaptations of workers’ theatre through the project Birdie Danse Macabre. Developed during a residency at IASPIS (Swedish Arts Grants Committee), the work examined the “frankenchicken” as a symbol of the human and environmental cost of industrial food production in the Capitalocene. Combining historical research into Swedish workers’ theatre, verbatim performance techniques, and participatory narrative devices, the presentation demonstrated how historic forms of creative resistance can be reimagined within contemporary design practice. The lecture-performance was followed by a moderated discussion and audience Q&A.